An analysis of fat-related and fiber-related behavior in men and women with type 2 diabetes mellitus: key findings for clinical practice - Hendrychova, Tereza; Vytrisalova, Magda; Vlcek, Jiri; Smahelova, Alena; Kubena, Ales Antonin (Patient preference and adherence, 2013)
BACKGROUND: Despite the efforts of health care providers, adherence of patients with type 2 diabetes to the recommended diet is poor. The aim of this study was to describe the eating habits with emphasis on fat and fiber-related behavior (FFB) as well as the relationship between FFB behavior and parameters of diabetes control in men and women with type 2 diabetes mellitus. METHODS: The subjects in this observational cross-sectional study were 200 patients (54.5% male, mean age 66.2 ± 10.1 years, mean Diabetes Control and Complications Trial [DDCT] glycosylated hemoglobin [HbA1c] 7.6% ± 1.7%) recruited from diabetes outpatient clinics in the Czech Republic. The subjects filled out the Fat- and Fiber-related Diet Behavior Questionnaire. The most recent patient data on diabetes control and drug therapy were derived from patient medical records. RESULTS: Patients tend to modify the dishes they are used to, rather than remove them completely from their diet and replace them by other types of foods. It is easier to perform healthier fat-related behaviors than fiber-related ones. Women scored significantly better than men on the fat-related diet habits summary scale (P = 0.002), as well as on "modify meat" (P = 0.001) and "substitute specially manufactured low-fat foods" (P = 0.045) subscales. A better score on the fat-related diet habits summary scale was significantly associated with higher HbA1c (ρ = -0.248; P = 0.027) and higher waist circumference (ρ = -0.254; P = 0.024) in women. CONCLUSION: Type 2 diabetes patients are likely to vary in their FFB behavior, and their dietary habits depend on gender. Health care professionals should pay attention to these facts when providing specific education. Emphasis should be placed on how to increase the fiber intake in diabetic patients.
Keywords: adherence; Fat- and Fiber-related Diet Behavior Questionnaire; dietary fiber; dietary fat